Primary hyperparathyroidism: review and recommendations on evaluation, diagnosis, and management. A Canadian and international consensus. Issue 1 (January 2017) - Khan, A.; Hanley, D.; Rizzoli, R.; Bollerslev, J.; Young, J.E.M; Rejnmark, L.; Thakker, R.; D'Amour, P.; Paul, T.; Van Uum, S.; Shrayyef, M.; Goltzman, D.; et al.
Abstract The purpose of this review is to assess the most recent evidence in the management of primary hyperparathyroidism (PHPT) and provide updated recommendations for its evaluation, diagnosis and treatment. A Medline search of "Hyperparathyroidism. Primary" was conducted and the literature with the highest levels of evidence were reviewed and used to formulate recommendations. PHPT is a common endocrine disorder usually discovered by routine biochemical screening. PHPT is defined as hypercalcemia with increased or inappropriately normal plasma parathyroid hormone (PTH). It is most commonly seen after the age of 50 years, with women predominating by three to fourfold. In countries with routine multichannel screening, PHPT is identified earlier and may be asymptomatic. Where biochemical testing is not routine, PHPT is more likely to present with skeletal complications, or nephrolithiasis. Parathyroidectomy (PTx) is indicated for those with symptomatic disease. For asymptomatic patients, recent guidelines have recommended criteria for surgery, however PTx can also be considered in those who do not meet criteria, and prefer surgery. Non-surgical therapies are available when surgery is not appropriate. This review presents the current state of the art in the diagnosis and management of PHPT and updates the Canadian Position paper on PHPT. An overview of the impact of PHPT on the skeleton and other target organs is presented with international consensus. Differences in the international presentation of this condition are also summarized.